CO- INFECTION AND RISK FACTOR OF HEPATITIS B AND HEPATITIS C VIRUS IN HIV INFECTED PATIENTS IN CENTRAL INDIA - DR. RAJENDRA KUMAR JAIN; DR. HIMANSHU SHARMA; DR. VIRENDRA KUMAR SHARMA; DR. SHWETA SHARMA (International Journal of Pharma and Bio Sciences, 2014)
Improved survival due to success of highly active anti retroviral therapy (HAART) has enabled chronic viral hepatitis to become a major source of co-morbidity in Human Immunodeficiency Virus (HIV) infected population. Presently Hepatitis B virus (HBV), Hepatitis C virus (HCV) and Human Immunodeficiency Virus (HIV) co infection prevalence is unknown in central India, so we evaluated HBV and HCV prevalence and risk factors among HIV positive patients attending Anti Retroviral Treatment (ART) centre. Out of 1500 cases (median age 33 Years, 68% male, M: F; 1020:480). HBV/HIV co-infection in 45/1500 (3%), HCV/ HIV co-infection in 25/1500 (1.7%) and triple infection (HBV/HCV/HIV) in 3/1500 (0.2%) patients. Most common route of transmission (60%) was unsafe sex in HBV co infection and history of intravenous drug use (IDU) in other two groups. Prevalence of HBV and HCV in HIV positive patients is low in central India. Screening for these viruses in all the HIV infected individuals and their sexual partners should be done at the earliest.